2020
DOI: 10.1108/caer-04-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on China's macroeconomy and agri-food system – an economy-wide multiplier model analysis

Abstract: PurposeThe purpose of this study is to assess the potential economic cost of the COVID-19 pandemic on China's macroeconomy and agri-food system and provide policy recommendations to stimulate economic growth and agri-food system development.Design/methodology/approachAn economy-wide multisector multiplier model built on China's most rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 3 publications
4
126
0
Order By: Relevance
“…Zhang et al [ 4 ] pointed out that the COVID-19 has the potential to impact nearly every facet of the agricultural industry, including the massive unsalable agricultural products, the low development of livestock sector, the blocked supply of agricultural products, the obstruction of agricultural product trade, the decrease in farmers' income, and the increase in poverty in rural areas. Zhang et al [ 5 ] analyzed the impact of COVID-19 on China's food supply and nutrition security. They pointed out that the hiccup in food and nutrition security is not severe in the short term because of the sufficient stocked food before the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 4 ] pointed out that the COVID-19 has the potential to impact nearly every facet of the agricultural industry, including the massive unsalable agricultural products, the low development of livestock sector, the blocked supply of agricultural products, the obstruction of agricultural product trade, the decrease in farmers' income, and the increase in poverty in rural areas. Zhang et al [ 5 ] analyzed the impact of COVID-19 on China's food supply and nutrition security. They pointed out that the hiccup in food and nutrition security is not severe in the short term because of the sufficient stocked food before the outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, according to reports in different countries of the world, it can be concluded that the impact of COVID-19 on agriculture has been lower than other economic sectors such as tourism, industry, and construction ( Diao and Wang, 2020 ; Maliszewska et al, 2020 ; Zhang et al, 2020 ). Diao and Wang ( Diao and Wang, 2020 ) estimated the declines in GDP due to COVID-19 in the construction, services, industry, manufacturing and agriculture sectors in Myanmar at 82%, 56%, 52%, 40% and 14%, respectively.…”
Section: Covid-19-induced Agriculture Vulnerabilitymentioning
confidence: 99%
“…Diao and Wang ( Diao and Wang, 2020 ) estimated the declines in GDP due to COVID-19 in the construction, services, industry, manufacturing and agriculture sectors in Myanmar at 82%, 56%, 52%, 40% and 14%, respectively. Zhang et al (2020) estimated that under the influence of COVID-19, China's GDP fell 6.8% in the first quarter of 2020 compared to 2019, while the agri-food system's economic loss equaled 7% of its value added. As China's economy recovered in the second and third quarters of 2020, the growth rate of the value-added agri-food system increased, but remained moderate.…”
Section: Covid-19-induced Agriculture Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, agriculture is slower than in other sectors. [2] Research on the impact of the Covid-19 pandemic on SMEs has also been in Sri Lanka. The study reveals that it requires high economic costs to overcome the effect of the COVID-19 disaster on SMEs in Sri Lanka.…”
Section: Previous Researchmentioning
confidence: 99%